SWEET PRODUCTS (SALADS) FROM CARROTS; COMMUNITY SERVICE SESSION OF BARAKATI VILLAGE: PRODUK MANISAN (SALAD) DARI WORTEL; SESI PENGABDIANPADA MASYARAKAT DESA BARAKATI - Tahir, Muh (PT. ROCE WISDOM ACEH, 2024)
This activity presents information and knowledge on the processing of one of the horticultural commodities, namely carrots. Carrot plants on a small scale can be cultivated in the yard of the house with polybag like medicinal plants and other flowers. Routine maintenance can be carried out to produce tubers which are then processed into candied products. Candied carrot or salad are made with other additives such as sugar, salt, sesame, butter and emulsifiers. The resulting candied carrots have a unique taste, a thick soup with nutritional content that is beneficial for heart and eye health.